Traveling mercies : some thoughts on faith - Lamott, Anne. (New York : Anchor Books, 2000)
The author describes the lifelong process through which she came to believe in God, discussing the battles she fought with alcohol, food disorders, and the loss of loved ones, and following her search for the spiritual path.
Library Journal, January 1999
Publisher's Weekly, December 1998
Booklist, January 1999
New York Times, March 1999
Kirkus Review, November 1998
Adult
Keywords: Lamott, Anne -- Religion; Women novelists, American -- 20th century -- Biography; Christian biography -- United States; Mothers and sons -- United States; Faith; Lamott, Anne; Women novelists -- Biography; American novelists -- Biography; Christian biography; Mother-son relationship; Faith